PENGABDIAN DESA MELALUI PEMBUATAN DAN PEMUTARAN FILM DOKUMENTER DI KELURAHAN REBAH TINGGI KOTA PAGARALAM - Annada Nasyaya; Agung Osama Dillah; Auliya Al Muhsonna; Muhammad Reynaldi Agustian; Putri Azzahra; Putri Iswa Nabilah; Zega, Prima Harlit; Rahmad Hidayah Abellah (Bajang Institute, 2024)
Indonesia is a country with a variety ofuniqueness, this cannot be separated from the various tribes, races, customs and cultures that were born and spread throughout the archipelago. Likewise in one of the sub-districts inPagar Alam City, namely Reba Tinggi Sub-district. Born and grown as a sub-district with history and customs that are still inherent in the local community. Therefore, the Reba TinggiSubdistrict PMD Team took the initiative to visualize this in a documentary film containing history, traditional figures, culture and manyother things that are customary in the subdistrict. This documentary film was made based on a well-planned framework from the pre-productionsection which prepared all kinds of concepts and ideas and various kinds of manufacturing permits to smooth the production process, then to theproduction process where there were many shooting areas and interviews with traditional leaders and residents for data. valid, up to quite complex post-production. This documentary film was made with the aim of increasing knowledge about the history and existence of Reba TinggiVillage so that future generations can enjoy various kinds of local wisdom in Reba Tinggi Village.